HUBUNGAN ANTARA KECENDERUNGAN GANGGUAN PSIKIATRI MENURUT SCL - 90 DENGAN EATING DISORDERS PADA REMAJA DI MADRASAH ALIYAH NEGERI 1 YOGYAKARTA - SUSANTI P.A.E; MARCHIRA C.R; AGUSNO M (LP2MTBM MAKARIOZ, 2021)
The purpose of this study is to find out the relationship between psychiatric symptoms according to SCL-90 and the tendencyof eating disorders in adolescents in Madrasah Aliyah Negeri 1 Yogyakarta. This research method is an observational studywith cross-sectional design. The subjects of this study were students of grade X and XI MAN I Yoyakarta. Eating disorderstendencies were assessed with the instrument Eating Attitudes Test-26 (EAT-26) and psychiatric symptoms were assessedwith Symptoms Check List-90 (SCL-90). The data is analyzed with univariate, bivariate and multivariate. The results of 185adolescents found a meaningful relationship between the tendency of psychiatric disorders, especially the domain ofdepression, interpersonal sensitivity and additional symptoms with eating disorders (p=0.008; p=0.030; p= 0.001) inadolescents at Madrasah Aliyah Negeri 1 Yogyakarta. The results of the logistic multiple regression test showed a significantinfluence between additional symptoms and bmi was not ideal against eating disorders (p=0.039; p=0.040). There is nostatistically meaningful relationship between the tendency of psychiatric disorders according to SCL-90 and eating disorders.But there is a meaningful association in the domain of depression, interpersonal sensitivity and additional symptoms witheating disorders.